Development of E-module Application Smartphone with Socioscientific Issue (SSI) in Biofuels - Erny Rohayu; Isana Supiah Yosephine Louise (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the lack of ability of chemistry teachers to prepare online learning media that requires students to achieve 4.0 technological developments. This research aims to create a valid and practical socio-scientific issue-based learning media. The development of this socioscientific-based e-module is carried out by applying the ADDIE (analysis, design, development, implementation and evaluation) development model. The data collection technique used in product validation is the questionnaire method. Theoretical validation in this study was carried out by expert lecturers, chemistry teachers, and peer reviewers. The validation of expert lecturers is described descriptively to the criticisms and suggestions given. Based on the validation result of the chemistry teachers and peer reviewers, respectively 88.8% and 87.9%, it was stated that the electronic module (e-module) was very eligible. The practicality of the e-module is known from the results of the student response questionnaire, which was a very eligible category. Based on the overall assessment results, the e-module product is feasible to be implemented in chemistry learning.